Comparison of perioperative and functional outcomes of robotic partial nephrectomy for cT1a vs cT1b renal masses. (11th August 2017) - Reynolds, Christopher R.; Delto, Joan C.; Paulucci, David J.; Weinstein, Corey; Badani, Ketan; Eun, Daniel; Abaza, Ronney; Porter, James; Bhandari, Akshay; Hemal, Ashok K.
Abstract : Objective: To compare perioperative and functional outcomes of patients with cT1a or cT1b renal masses undergoing robotic partial nephrectomy (RPN) in a large multi‐institutional study Patients and Methods: The present retrospective Institutional Review Board‐approved multi‐institutional study utilised a prospectively maintained database to identify patients undergoing RPN by six surgeons for a solitary cT1a ( n = 1 307) or cT1b ( n = 377) renal mass from 2006 to 2016. Perioperative and renal function outcomes at discharge and at a median follow‐up of 12.2 months were compared in univariable and multivariable regression analyses adjusting for surgeon performing the procedure and date of surgery. Results: In univariable analysis, cT1b masses were associated with longer operative time (190.0 vs 159.0 min, P < 0.001), longer warm ischaemia time (18.8 vs 15.0 min, P < 0.001), higher estimated blood loss (150.0 vs 100.0 mL, P < 0.001), more intraoperative complications (5.6% vs 2.4%, P = 0.034), and more surgical postoperative complications (10.1% vs 5.7%, P =0.002). Results were similar in multivariable analysis with additional findings including more overall postoperative complications (odds ratio 1.55, P = 0.015) and longer length of stay ( P < 0.001) associated with cT1b masses. There were no differences in the risk of progression of chronic kidney disease stage at 12.2 months, positive surgical margins, or major postoperative complications. Conclusions: Although our study shows a longer operative time, longer warm ischemia time, and higher complication rate for patients undergoing RPN for cT1b renal masses, the magnitude of these differences is small. RPN should be considered for cT1b lesions when anatomical and spatial location allow for a feasible procedure.